2006
DOI: 10.1590/s0036-46652006000100011
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Taenia solium metacestode IgG antibodies in serum samples from inhabitants of a central-western region of Brazil

Abstract: SUMMARYA total of 354 serum samples from inhabitants who frequent the Clinical Laboratory in Catalão, Goiás, in the central-western region of Brazil, were collected from June to August, 2002. The samples were evaluated by indirect immunofluorescence antibody tests and an enzyme linked immunosorbent assay in order to detect anti-Taenia solium metacestode IgG antibodies. Reactive and inconclusive samples were tested by Western blotting (WB). Considering WB as a confirmation, the frequency of antibodies in the se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 16 publications
0
8
0
2
Order By: Relevance
“…(Taeniidae family) and to the presence of common antigenic components between these species (Montenegro et al 1994). Cross-reactivity in S. stercoralis infections can be related to the infection of these individuals with both species (T. solium and S. stercoralis), as the city of Uberlândia and the "Triângulo Mineiro" region is considered endemic in terms of human cysticercosis, according to Silveira-Lacerda et al (2002) and Oliveira et al (2006), and hyperendemic for S. stercoralis according to Machado and Costa-Cruz (1998).…”
Section: Discussionmentioning
confidence: 99%
“…(Taeniidae family) and to the presence of common antigenic components between these species (Montenegro et al 1994). Cross-reactivity in S. stercoralis infections can be related to the infection of these individuals with both species (T. solium and S. stercoralis), as the city of Uberlândia and the "Triângulo Mineiro" region is considered endemic in terms of human cysticercosis, according to Silveira-Lacerda et al (2002) and Oliveira et al (2006), and hyperendemic for S. stercoralis according to Machado and Costa-Cruz (1998).…”
Section: Discussionmentioning
confidence: 99%
“…Although our study was conducted with well‐documented samples from NC patients or from patients with heterologous infections or apparently healthy individuals, previous studies using whole metacestode extracts have demonstrated that either ELISA or immunoblot are useful tools for epidemiological screening of NC (Silveira‐Lacerda et al. 2002; Oliveira et al. 2006; Prestes‐Carneiro et al.…”
Section: Discussionmentioning
confidence: 99%
“…was thus demonstrated (12,15). These antigens are responsible for the cross-reactivity between both parasites, even though previous studies using whole-metacestode extracts have demonstrated that both the ELISA and immunoblotting may be considered useful tools for epidemiological screening of NC (30,34,38). Therefore, as cross-reactivity between T. solium and E. granulosus occurs in screening tests such as the ELISA, additional assays are required to validate the results, preferentially by using alternative assay designs with purified and more specific antigens.…”
Section: Discussionmentioning
confidence: 86%
“…Considering that there is minimal phylogenetic proximity between Taenia sp. and Strongyloides sp., these results may be related to the presence of infections with both species (T. solium and S. stercoralis) in these individuals, since human cysticercosis is considered endemic (30,38) and S. stercoralis hyperendemic (26) in the city of Uberlândia within the Triângulo Mineiro region.…”
Section: Discussionmentioning
confidence: 97%